The Analysis of public output: a conference of the Universities-National Bureau Committee for Economic Research - Margolis, Julius; Universities-National Bureau Committee for Economic Research; National Bureau of Economic Research (New York: National Bureau of Economic Research; distributed by Columbia University Press, 1970)
Papers in this conference volume, applied economic analysis to the formulation and implementation of public programs, such as decentralization of government and the correction of postal service inefficiencies, as well as to the solution of such problems as high accident rates due to highway congestion. The Analysis of Public Output deals with four general categories of public economics- the theory of market failure and public action; distributional aspects of public decisions; intergovernmental fiscal relations; and application of analysis to specific problems and general approaches.
Includes bibliographical references and index.
hza 22/06/2018
Loans
Keywords: Expenditures, Public; Public interest; Government spending policy